IDENTIFIKASI JENIS-JENIS GASTROPODA DI KAWASAN HUTAN MANGROVE DESA BULALO KECAMATAN KWANDANG KABUPATEN GORONTALO UTARA - Latjompoh, Masra (Sainstek, 2009)
Is this research about the problems of the types of gastropoda around the mangrove forest Bulalo Village, Kwandang with of Gorontalo District. This research purposed to find about the gastropoda types in mangrove forest Bulalo village Kwandang, North Gorontalo District. This research is descriptively using survey method. To find and know directly about data in location. So me using observation technique. To have a sample in this research, with taking all of the sample me find in exploration process with purposive sampling technique. Analysis of data using determination keys in zoology lab. biology Gorontalo State University. Kata Kunci : Gatropoda, Mangrove